Validity of Cooking in Microwave and Gamma-irradiation on Highly Virulent Aeromonas hydrophila Isolates in Basa Fish Fillet - El-Demerdash, Azza S.; EL-Sheikh, Soad H.; Fahmy, Hanan A. (Journal of Advanced Veterinary Research, 2023)
The purpose of the study was to verify the existence and pathogenicity of Aeromonas hydrophila (A. hydrophila) in fish by validating the bactericidal effects of microwave and Gamma radiation on infected fish fillets. A total of 100 frozen Basa fish fillet samples were collected randomly from different markets in Zagazig, Sharkia Governorate, Egypt, and subjected to microbiological examination. The results revealed a 14% prevalence rate of A. hydrophila in fish fillets, which were tested for the presence of seven virulence genes: aerA, act, ast, alt, hyl, ahhR, and ahh1. All isolates exhibited traits related to virulence. The most predominated gene was ast (64.2%), followed by aerA, act, hyl, and ahhR (57.14% for each). Then, an experimental protocol for several treatments showed that Gamma radiation at a dose of 1 kGy decreased the count of A. hydrophila in fish fillets by 4.4 log10 CFU/g whereas doses of 2 and 3 kGy eradicated the pathogen. The same positive effect was recorded towards the microwave after cooking for 1, 2, and 3 minutes. Therefore, using microwave cooking and Gamma-irradiation alone and in combination with other decontamination methods may be more efficient in lowering the pathogen counts in fish meat.